GAYA BAHASA IKLAN PRODUK PT. UNILEVER INDONESIA: Suatu Tinjauan Semantik dan Pragmatik - Silvia Yurnianti; Ermanto Ermanto; Zulfadhli Zulfadhli (Jurnal Bahasa dan Sastra, 2012)
The purpose of this article is (1) to describe literary style in product advertisement of PT. Unilever Indonesia, (2) to describe the context of literary style in product advertisement of PT. Unilever Indonesia. This research data is 52 advertisements that are gotten by downloud with youtube site. The data collection is transcripted, after that identifying the data and also the context of literary style in product advertisement of PT. Unilever Indonesia, then it is classified base on the same literary style and context. The research findings are first, there are 7 comparison literary styles in product advertisement of PT. Unilever Indonesia that is devided into literary style of simile, metaphora, personification, metonnimi, sinecdoc pars pro toto, hiperbola, and paradocs. Second, there are 8 (eight) comparison literary styles in product advertisement of PT. Unilever Indonesia that are climax, non-climax, repetition, paralism, alliteration, ellipsis, ironi literary style, and retoris question. The context of literay style usage in Product advertisement of PT. Unilever Indonesia is to explain special quality of product to convice and persuade the audience and society when they see the product advertisement of PT. Unilever Indonesia to use the product.